Developing icollect mobile (android and iphone-based) application for arabic language teaching - Md Ghalib, Mohd. Feham; Hassan, Haslina; Sahrir, Muhammad Sabri; Mat Daud, Nuraihan; Mohin, Mohaida; Ayu, Media Anugerah (IDOSI Publications, 2014)
The present study presents the steps taken to produce a mobile e-portfolio for Arabic learners, which is named iCollect. Common e-portfolio features and suggestions by e-portfolio experts were considered when designing iCollect. Its prototype, which was web-based, was shown to a sample of the target group. They expressed their preferences for Dashboard, Profile, Settings, Journals, Artifacts, Portfolio, Connect, Members and Question functions which have been integrated with the relevant Web 2.0 tools. Their feedback was used to improve iCollect further. The mobile version took into account the smaller phone screen size. The availability of Arabic scripts makes it suitable for learning and teaching Arabic.